MEDIA PENDIDIKAN: Peran dan Fungsinya dalam Pembelajaran - Umar, Umar (TARBAWIYAH, 2013)
Media, originally known simply as an aid in learning activities that serve to provide a visual experience to students, increase learning motivation, clarify, and simplify the complex and abstract concepts become more simple, concrete and easy to understand. Now, in addition to tool also has become a concept of learning technologies or its use as a learning resource in the learning process.Kata Kunci: Role, Function and Learning MediaÂ